Oral Rehabilitation with Zygomatic Implants in a Patient with Cleft Palate - Guilherme José Pimentel Lopes de Oliveira; Mariana Schaffer Brackmann; Larissa Carvalho Trojan; Paulo Domingos Ribeiro Júnior; Luis Eduardo Marques Padovan (Case Reports in Dentistry)
Edentulous patients with an atrophic maxilla associated with lip-palate fissures have unpredictable results after undergoing grafting procedures. In situations where the atrophic maxilla does not adequately allow reconstruction, the use of zygomatic implants has been indicated, and probably these implants can be indicated for the rehabilitation of patients with lip-palate fissures. This case report describes the oral rehabilitation treatment of a patient with a lip-palate cleft treated with zygomatic implants and implant-supported fixed prosthesis with two years of follow-up. A 65-year-old female patient had a lip-palate cleft and previously underwent surgery to close the cleft. The patient had a severely atrophic maxilla and had difficulty adapting to a removable total prosthesis. Due to the small amount of bone remaining and extensive fibrous tissue in the palate region, a rehabilitation with conventional implants associated with zygomatic implants was chosen. Two zygomatic implants and a conventional implant were placed on the right side, and a zygomatic implant and conventional implant were placed on the left side; these implants were later activated by a protocol-type prosthesis. The zygomatic implants provided an adequate aesthetic and functional outcome of the prosthesis in a patient with cleft palate.